The Importance of Digital Literacy Skills in the Context of Learning English for Specific Purposes: A Systematic Review - Luh Putu Diantari Kusuma Dewi; I G A Lokita Purnamika Utami; Made Hery Santosa (Publikasi Indonesia, 2024)
In today's landscape of language education, the integration of digital literacy (DL) with English for Specific Purposes (ESP) has gained significant importance. In an increasingly digitised world, proficiency in digital literacy is becoming indispensable for effective communication and language acquisition. This article presents a systematic review synthesising insights from various scholarly publications to clarify the crucial importance of digital literacy skills in enhancing the effectiveness of ESP instruction and improving learning outcomes. Drawing upon a range of empirical studies and theoretical frameworks, the researcher explores the multifaceted impacts of digital literacy on ESP learners, educators, and instructional practices. The analysis highlights the significant impact of incorporating digital tools, resources, and teaching methods into ESP programs. It emphasises how they contribute to authentic language application, improved communication skills, and the advancement of professionals in specialised fields. By considering various viewpoints and empirical data, studies consistently demonstrate the effectiveness of integrating digital literacy into ESP programs. This fosters strong information literacy, digital tool proficiency, and effective communication and collaboration skills in ESP learners.